Protection of Semantic Organized Data. Encryption of RDF Graph - Galina Bogdanova; Todor Todorov; Nikolay Noev (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2014)
The problems of protection of semantic organized data and encryption of RDF graph are investigated. Technologies used in the construction of a semantic network are presented. XML-encryption and standardization of semantically structured content for XML signature are described. We perform encryption of XML data associated with the semantic representation of data for a kind of percussion instruments.